Modelling and simulation of D-class current-fed parallel resonant inverter for induction heating system (Aintelia Science Notes, 2022)
In the induction heating process, non-contact heating is carried out. Induction heating systems are used in heating, melting, surface hardening processes and applications such as cooking. Induction heating is based onMichael Faraday's Law of Induction. Compared to conventional heating methods, the induction heating method has advantages such as shorter processing time, uniform distribution of heat on the material, highefficiency and no explosion hazard. In order to realize induction heating, a variable magnetic field and a metal material placed in the magnetic field are needed. Voltage-fed or current-fed resonant inverters are frequentlyused to realize power conversion in induction heating and because of their low switching losses and zero current or voltage switching possibilities. In this study, D-class current-fed parallel resonant inverter, which is one of the resonant converter types, is used. The operating states of the switching frequency below the resonant frequency, equal to the resonant frequency, and above the resonant frequency have compared. The simulation results were obtained by modeling the designed current source parallel resonance inverter with PSIM software. Thus, it has been observed that the phase difference between the output current and voltage in the parallel resonant inverter depends on the switching frequency. As a result of the operation of the resonant inverter at the resonant frequency, it has been determined that zero voltage switching is provided. Thus, it has been observed that maximum efficiency is achieved by preventing switching losses and the obtained results are presented.
Keywords: Induction Heating Systems; Parallel Resonance Inverters; PSIM